Highly reactive anti-myelin oligodendrocyte glycoprotein antibodies differentiate demyelinating diseases from viral encephalitis in children - Lalive, PH; Häusler, MG; Maurey, H; Mikaeloff, Y; Tardieu, M; Wiendl, H; Schroeter, M; Hartung, HP; Kieseier, BC; Menge, T (Multiple sclerosis, 2011)
Background: Myelin oligodendrocyte glycoprotein (MOG) may be implicated in the immunopathogenesis of multiple sclerosis (MS) inducing demyelination in the animal model of MS. In adults reported anti-MOG antibody frequencies have been variable across a number of studies and can also be detected in controls. Objective: To measure antibodies against MOG in paediatric patients with demyelinating disorders of the central nervous system and in controls. Methods: Serum antibodies against MOG and myelin basic protein were measured by ELISA, flow cytometry (FACS) and in the liquid phase in 11 children with acute disseminated encephalomyelitis (ADEM), 22 children with MS, seven children with acute viral encephalitis and 13 healthy controls. The serostatus of Epstein–Barr virus (EBV) infections were assessed. Results: Anti-MOG antibodies, measured either by ELISA or FACS were exclusively detected in children with demyelination. In ADEM these antibodies were highly reactive. Anti-MBP reactivity was detectable equally in all groups. The presence of either autoantibodies did not associate with EBV serostatus, age, gender or disease course. Conclusions: This study independently corroborates recently published results of seroprevalence and specificity of the assay. Due to their low sensitivity anti-MOG antibodies will not serve as disease-specific biomarkers, but could help to support the diagnosis of ADEM in difficult cases.